Analysis of misinformation in the context of the coronavirus vaccination in Brazil - Mendes, André Medeiros; Gomes-Jr, Luiz (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2022: Proceedings of the 28th Brazilian Symposium on Multimedia and the Web, 2022)
The misinformation circulating on social media regarding the coronavirus pandemic has been a obstacule in the fight against the disease, directly impacting the advancement of immunization in various parts of the world. This study sought to evaluate possible influences between vaccination rates in Brazil and social media interactions related to posts from questinable sources. Using econometric models, we measured the impact of questionable information about vaccines, considering geographic, political and social issues. The results show a negative impact on vaccination rates, with different variations depending on the political orientation of the posts considered, as well as a geographic inequality in terms of vulnerability to misinformation.